Public’s Legal Awareness on Child Marriage - Septi, Lia Eka; H., Rima Vien Permata; Rejekiningsih, Triana (International Journal Labs, 2023)
This study aims to conduct a qualitative analysis of the legal awareness of ethnic Javanese people on the practice of child marriage in Bumirejo Hamlet, Tapak Siring Village, Sukau District. Data collection was conducted through interviews, observations and documentation from parents and perpetrators of child marriage, as well as community leaders. This study shows that the low legal awareness of the Javanese ethnic community on the practice of child marriage is motivated by low education, economy, community habits, and self-will. There has been no effort from local community leaders to minimize the occurrence of child marriage so that the practice of child marriage still occurs.